FACTORS CONTRIBUTING TO READERS' UNDERSTANDING ON LITERARY WORKS - Meliana, - (2005)
This study investigated the readers' response to short stories namely: Razia Agustus, Bu Tam and Ziarah. Those short stories were taken from Sobron Aidifs short stories collection. Razia Agustus (2004). The study attempted to disclose the issues that the readers grasp from the short stories and factors contributinq to the readers' understancinq toward the issues they grasp from the stories. To investigate the phenomena, the writer used qualitative design by ernployinq descriptive method. The data were collected from the responses of 10 students. Using the framework developed by Rosenblatt, the result of the study indicated that the students grasp two main issues from the short stories namely: political and social. Referring tu categorization by Beach, the obtained data indicated that there were only three factors that contribute to the readers' understanding on the issues they grasp from the short stories which are: other texts. related experience, and personal attitudes. One factor that did not appear on this study was literary prototypes. The category did not appear because the students were not reading rm:::h literary texts. The study suggested that the readers transact not only with texts but also with social contexts around them.